Typing of Uncultured Isolates of Coxiella burnetii and Coxiella-Like Microorganisms Associated with Ticks Using 16S rRNA Gene Nucleotide Sequence Analysis - Yu. A. Panferova; N. K. Tokarevich; O. V. Blinova; A. A. Nafeev; E. I. Sibaeva (Проблемы особо опасных инфекций, 2023)
The causative agent of Q fever, the intracellular pathogen Coxiella burnetii, is found almost worldwide; many types of blood-sucking ticks that are dangerous to animals and humans are involved in the circulation of the pathogen. Using molecular-genetic methods, closely related species of microorganisms of the genus Coxiella sp. have been discovered, some of which are endo-symbionts of ticks, and some can survive in the human body, causing an infectious process. The existence of species whose genes are similar in nucleotide sequence to those of C. burnetii makes it difficult to diagnose the pathogen in arthropod vectors. The aim of this work was to consider the use of PCR and sequencing of an extended 16S rRNA gene fragment for molecular diagnostics and differentiation of C. burnetii from Coxiella-like microorganisms. Materials and methods. Individual samples of blood-sucking ticks were examined to detect bacteria of the genus Coxiella sp. applying standard PCR. For positive samples, an extended fragment of the 16S rRNA gene was obtained and examined by sequencing and multiple alignment with homologous sequences. Results and discussion. Of the 96 examined ticks collected in the Ulyanovsk Region, one was positive for the presence of C. burnetii DNA and one – for the presence of Coxiella sp. The greatest similarity for the C. burnetii isolate was noted in comparison with Western European strains, for the Coxiella-like microorganism - with closely related bacteria from ticks of the same species. Unique polymorphisms for the detected microorganisms were identified. It has been established that genus-specific primers to the 16S rRNA gene fragment are able to amplify not only bacteria of the genus Coxiella sp., but also genetically distant species. Analysis of the sequence of the extended 16S rRNA gene fragment makes it possible to differentiate C. burnetii from Coxiella-like microorganisms; some gene polymorphisms appear to have arisen through microevolution in different geographic regions. In the European part of the Russian Federation, Coxiella-like bacteria have been uncovered for the first time.